A hierarchical and gradient structured supersorbent comprising three-dimensional interconnected porous fibers for efficient oil spillage cleanup. Issue 24 (6th June 2016) - Zhao, Yueyue; Miao, Xiaran; Lin, Jinyou; Li, Xiuhong; Bian, Fenggang; Wang, Jie; Yue, Baohua
Abstract : A hierarchical and gradient structured supersorbent consisting of three-dimensional interconnected porous polystyrene fibers was fabricated via successive electrospinning for efficient oil spillage cleanup. Abstract : The global environmental challenge includes calls for emerging materials that can effectively clean up oil spillage from water. The fabrication and upgrading of sorbent materials with a high sorption capacity and excellent oil/water separation performance has become a high-profile topic today. Herein, for the first time, such a material is presented by assembling three-dimensional interconnected porous polystyrene fibers with a hydrophobic and oleophilic surface via successive electrospinning, showing superior performance in oil spillage cleanup. The key innovation point applied in this study is to produce a gradient structured system between these hierarchical fibres that can form gradient inter-fiber voids, resulting in a gradient capillary action force in the sorption process for oils. The as-designed super sorbent material exhibits high sorption capacity, as well as ultrafast sorption rates for various oils. The initial oil sorption amounts of the super sorbent material for pump oil, colza oil and diesel oil were approximated to 307.24 g g −1, 224.31 g g −1, and 84.52 g g −1, respectively, which are superior to those of other normal fibrous sorbents. Furthermore, the as-designed material, supported on a nonwoven fabric substrate exhibits outstanding performance for removing emulsified oil from water. More importantly, this superior material could be applied in industrial production because of its low cost and simple fabrication procedure. This study presents a facile strategy for the fabrication of efficient oil sorbents, providing a novel means for the upgrading of engineered sorption materials.